2020
DOI: 10.1038/s41598-020-58588-1
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Influenza A Virus Exposure in an Elementary School

Abstract: Influenza contributes significantly to childhood morbidity and mortality. Given the magnitude of the school-aged child population, a sizeable proportion of influenza virus transmission events are expected to occur within school settings. However, influenza virus activity in schools is not wellunderstood, likely due to our limited ability to accurately monitor for respiratory viruses without disrupting the school environment. In this study, we evaluated the use of a bioaerosol sampling method to noninvasively d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 58 publications
3
45
2
Order By: Relevance
“…After that, similar epidemiological studies were also performed in hospitals, with similar results obtained [41]. Similarly, a recent study performed in an elementary school in the USA reported that influenza virus genome was detectable in aerosols (10 1 -10 4 genome copies/m 3 air) sampled at different locations during the influenza season [42], suggesting that the air is an important vector for virus transmission in schools.…”
Section: Environmental Transmission Through the Airsupporting
confidence: 62%
“…After that, similar epidemiological studies were also performed in hospitals, with similar results obtained [41]. Similarly, a recent study performed in an elementary school in the USA reported that influenza virus genome was detectable in aerosols (10 1 -10 4 genome copies/m 3 air) sampled at different locations during the influenza season [42], suggesting that the air is an important vector for virus transmission in schools.…”
Section: Environmental Transmission Through the Airsupporting
confidence: 62%
“…We concluded that the mode of transmission between the index patient and the secondary cases in this cluster was either through contaminated common objects or virus aerosol, since all three pairs shared the same squash hall, which is a small and confined space with poor ventilation, where strenuous physical activity is performed, during which shedding and aerosolisation of the virus could be increased [4, 1012]. Moist and warm atmosphere coupled with turbulent air flow generated by intense physical activity could extend the lifetime of virus-bearing droplets and eventually produce residues that may stay suspended in the air for hours [13, 14].…”
Section: Discussionmentioning
confidence: 99%
“…A striking example of long range aerosol transmission inside a building and to adjacent buildings were the clusters of SARS cases at Amoy Gardens and Prince of Wales Hospital in Hong Kong in 2003 ( Li et al, 2005 , Chu et al, 2005 , Yu et al, 2004 , Lee et al, 2003 ). Influenza virus remains infectious in aerosols across a broad range of relative humidity ( Coleman and Sigler, 2020 ), and this route has been used to explain transmission in hospitals and aircrafts ( Moser et al, 1979 ; Blachere et al, 2009 ), which has been confirmed by epidemiological investigation, fluid dynamic models and animal models ( Coleman and Sigler, 2020 ; Wong et al, 2010 , Mubareka et al, 2009 ). Influenza virus was also identified in the air of an emergency department 3 h after an infectious patient has left the area ( Blachere et al, 2009 ).…”
Section: Introductionmentioning
confidence: 94%